PERAN PUSAT PELATIHAN PERTANIAN DAN PEDESAAN SWADAYA DALAM MENINGKATKAN HASIL PRODUKSI DAN PENDAPATAN PETANI HORTIKULTURA STUDI: P4S BULUBALLEA, KECAMATAN TINGGI MONCONG, KABUPATEN GOWA, SULAWESI SELATAN (The Role of the Self-Help Agricultural and Rural Training Center in Increasing Production Yields and Income of Horticultural Farmers Case : P4S Buluballea, Subdistrict Tinggi Moncong , Gowa Regency, South Sulawesi) - ICHSAN, NURUL ANNISA; ANIH, RAHMAD; NADJA, RAHMAWATY A (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2024)
This study aims to 1) analyze the role of P4S in increasing the production and income of farmers, 2) determine the production and income of horticultural farming and 3) analyze the relationship between the role of P4S with the level of production and income of horticultural farmers in Tinggi Moncong District. This research was conducted with descriptive quantitative method with data collection using survey method conducted in Tinggi Moncong sub-district. The results concluded that 1) the production level of farmers in Tinggi Moncong Sub-district increased by 2-3 tons per hectare after joining P4S, proving that after becoming a member of P4S the productivity and income of farmers increased.  2) From the results of the correlation test using Sperman analysis, the significance value between the facilitator variable and the increase in production and income is 0.685, which indicates a strong relationship between the two variables. For the motivator variable is 0.681, which means that the level of strength of the relationship (correlation) between the motivator variable and the increase in production and income of farmers is at a strong level. From the results of the correlation test using Sperman analysis, the significance value between the facilitator variable and the increase in production and income is 0.685, which indicates a strong relationship between the two variables. For the motivator variable is 0.681, which means that the level of strength of the relationship (correlation) between the motivator variable and the increase in production and income of farmers is at a strong level.